2016
DOI: 10.3329/imcj.v9i1.27637
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CTX-M ? lactamases among Gram negative bacteria in a tertiary care hospital in Bangladesh

Abstract: Extended spectrum beta lactamases (ESBLs) produced by Gram negative bacteria are mainly mediated by three important genes, namely TEM, SHV and CTX-M. In this study, we used a multiplex PCR to determine the prevalence of CTX-M and its subgroups CTX-M-3, CTX-M-14, among the members of Enterobacteriaceae family and in Pseudomonas spp that were isolated from different clinical samples in a tertiary care hospital in Bangladesh. A total of 300 culture positive clinical isolates were selected for the study. Out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…This is similar to Jordan et al, [5] . Yasmin et al, [6] found that among 120 cases, majority 86 (71.6%) were benign, but alarming number 30 (25.0%) were malignant, remaining 4 cases were borderline. The commonest histological pattern observed in the study was epithelial tumors (61.6%).…”
Section: Discussionmentioning
confidence: 98%
“…This is similar to Jordan et al, [5] . Yasmin et al, [6] found that among 120 cases, majority 86 (71.6%) were benign, but alarming number 30 (25.0%) were malignant, remaining 4 cases were borderline. The commonest histological pattern observed in the study was epithelial tumors (61.6%).…”
Section: Discussionmentioning
confidence: 98%